2017
DOI: 10.1007/s11524-017-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Neighborhood Safety Is Associated with Poor Sleep Health among Gay, Bisexual, and Other Men Who Have Sex with Men in Paris, France

Abstract: Recent studies have examined sleep health among men who have sex with men (MSM), but no studies have examined associations of neighborhood characteristics and sleep health among this population. The purpose of this study was to examine associations between perceived neighborhood safety and sleep health among a sample of MSM in Paris, France. We placed broadcast advertisements on a popular smartphone application for MSM in October 2016 to recruit users in the Paris (France) metropolitan area (n = 580). Users we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 46 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…Future examination of sleep disparities should also explicitly include transgender and gendernonconforming individuals. While more research is needed to understand mechanisms for sexual orientation disparities in sleep, emerging research has shown that social stressors, such as financial hardship [15] and unsafe neighborhoods [7], can influence sleep among gay, bisexual, and other MSM populations. Finally, because poor sleep health has been shown among LGB people of color, future research should examine sleep among homosexual and bisexual men and women of color.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Future examination of sleep disparities should also explicitly include transgender and gendernonconforming individuals. While more research is needed to understand mechanisms for sexual orientation disparities in sleep, emerging research has shown that social stressors, such as financial hardship [15] and unsafe neighborhoods [7], can influence sleep among gay, bisexual, and other MSM populations. Finally, because poor sleep health has been shown among LGB people of color, future research should examine sleep among homosexual and bisexual men and women of color.…”
Section: Future Researchmentioning
confidence: 99%
“…Among gay, bisexual, and other men who have sex with men (MSM) in London, about one third (34.6%) rated their sleep quality as poor, and about half (43.6%) reported sleeping less than 7 h on average nightly [3]. Among a sample of MSM in Paris, poor sleep was also common, including 44.7% who reported problems falling asleep [7].…”
Section: Introductionmentioning
confidence: 99%
“… 15 The results of a study conducted in France also found that poor sleep quality and short sleep duration are common among men who have sex with men. 16 However, few studies have been conducted to examine the relationships between sexual minority status and sleep quality among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Users were shown an advertisement with text encouraging them to complete an anonymous web-based survey. 10 In English the ad read, 'Looking to improve your health, and the health of those in your community? Share your thoughts with us on gay and bisexual men's health and have a chance to win e65!…”
Section: Methodsmentioning
confidence: 99%